2018
DOI: 10.1371/journal.pone.0205704
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation for the treatment of Alzheimer's disease: A systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundSeveral studies have demonstrated that repetitive transcranial magnetic stimulation (rTMS) may have a beneficial effect in Alzheimer’s disease (AD). Nevertheless, the clinical benefit of rTMS for AD remains inconclusive.ObjectiveThis systematic review and meta-analysis aimed to evaluate the efficacy and safety of rTMS in AD.MethodsWe searched PubMed, Embase and Cochrane for randomized controlled trials (RCTs) of rTMS for AD. We calculated pooled estimates of mean difference (MD) with 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 35 publications
6
62
0
5
Order By: Relevance
“…It was also notable that improvements in cognition in both groups did not correlate with improvements in mood as would most typically be expected. Multiple lines of evidence have supported the notion that rTMS has the capacity to improve cognition across different neuropsychiatric disorders (for example [40,41]) and our data here in a very preliminary way suggest that potentially iTBS may have more of a pro-cognitive effect than standard TMS approaches.…”
Section: Discussionsupporting
confidence: 65%
“…It was also notable that improvements in cognition in both groups did not correlate with improvements in mood as would most typically be expected. Multiple lines of evidence have supported the notion that rTMS has the capacity to improve cognition across different neuropsychiatric disorders (for example [40,41]) and our data here in a very preliminary way suggest that potentially iTBS may have more of a pro-cognitive effect than standard TMS approaches.…”
Section: Discussionsupporting
confidence: 65%
“…Finally, a variety of approaches to brain stimulation are under development. Non-invasive stimulation, including repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS), has shown some evidence of benefit on cognition in AD in two recent meta-analyses, although the modality of stimulation, target choice, and frequency used were heterogeneous 115116. In deep brain stimulation (DBS), electrodes are implanted to stimulate targeted regions.…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…The searches identified 6,504 published studies, and after screening the titles and removing duplicates, 41 potentially eligible studies were selected for a closer scrutiny by retrieving the full text. Finally, we included 10 MAs (Lee et al, 2009;Alves et al, 2013;Rao et al, 2014;Zhou et al, 2015Zhou et al, , 2017Dong et al, 2018;Du et al, 2018;Huang et al, 2019;Jia et al, 2019;Wang et al, 2020). The study selection process is shown in Figure 1.…”
Section: Study Selection Processmentioning
confidence: 99%